1999
DOI: 10.1097/00006254-199909000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Use of Misoprostol in First and Second Trimester Abortion

Abstract: The use of misoprostol in medical termination of first and second term pregnancies and cervical priming in surgically induced termination of pregnancies has been studied extensively. A survey is given on the available literature (MEDLINE to May 1998) on the usage as a single medication or in combination with mifepristone or methotrexate. A review is given on literature concerning side effects and complications. Misoprostol is a most promising, cheap, and effective agent, which does not need cool storage like o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 61 publications
1
20
0
2
Order By: Relevance
“…1,3,6,[8][9][10][11][12][13][14][15][16][17][18] Use of misoprostol for second trimester pregnancy interruption was initially described by Jain et al in 1994; however, this regimen utilized a relatively low-dose misoprostol regimen (200 ug vaginally every 12 hours). 6 Several recent investigations have suggested that higher dose misoprostol regimens may be more efficacious.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1,3,6,[8][9][10][11][12][13][14][15][16][17][18] Use of misoprostol for second trimester pregnancy interruption was initially described by Jain et al in 1994; however, this regimen utilized a relatively low-dose misoprostol regimen (200 ug vaginally every 12 hours). 6 Several recent investigations have suggested that higher dose misoprostol regimens may be more efficacious.…”
Section: Discussionmentioning
confidence: 99%
“…6 Several recent investigations have suggested that higher dose misoprostol regimens may be more efficacious. 1,2,[8][9][10][11][12][13][14][15][16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it is inexpensive and storable at room temperature, and causes fewer side effects [6,7]. Much research has been carried out to defi ne the most effective and best tolerated dosage and route of administration, but previous studies have reported its success rate mostly within 24 hours [8,9]. In this study, we compared the effectiveness of intracervical laminaria plus vaginal misoprostol and vaginal misoprostol only with variable dosages by analyzing the rate of spontaneous gestational sac expulsion for medical abortion within 12 hours.…”
mentioning
confidence: 99%